Ensuring linearity of optical-reception system of infrared radiation thermometer - Гоц, Наталія Євгенівна; Петриченко, Геннадій Іванович; Кочан, Роман Володимирович; Приймак, Юлія Миколаївна (Technology audit and production reserves, 2014)
The need to ensure the linearity of the conversion function of the optical-reception system of the reference radiation thermometer was substantiated in the paper. The technique for ensuring the linearity of the conversion function of the optical-reception system of infrared radiation thermometer was proposed. It is based on the definition of deviations from linearity of conversion function of the optical-reception system of the radiation thermometer in several fixed temperature points, the formation of the temperature dependence of linearity corrections and their introduction into an output signal of the radiation thermometer. The experimental studies, the results of which have allowed to obtain the function of corrections for linearization of the output signal of radiation thermometer for temperature range 0÷419,51 K and spectral band 8÷14 microns were carried out. The proposed methodology is appropriate to apply in certification of reference radiation thermometers for implementing temperature scale transmission to working infrared radiation thermometers based on the Planck radiation law.